Serum/glucose starvation enhances binding of miR-4745-5p and miR-6798-5p to HNRNPA1 mRNA 3ʹUTR: A novel method to identify miRNAs binding to mRNA 3ʹUTR using λN peptide-boxB sequence - Tetsuyuki Takahashi; Mai Funamura; Shun Wakai; Takao Hijikata (Non-coding RNA Research)
Serum/glucose starvation causes complete loss of heterogeneous nuclear ribonucleoprotein A1 (hnRNP A1) without altering mRNA levels. However, the mechanisms driving hnRNP A1 downregulation during serum/glucose starvation are not yet well understood. Using the novel interaction between the λN peptide and boxB sequence (λN/boxB system) and miRNA microarray analysis, we aimed to identify specific-binding microRNAs (miRs or miRNAs) targeting HNRNPA1 mRNA 3ʹUTR under serum/glucose-starved conditions. Four miRNAs were identified as serum/glucose starvation-driven miRNAs for HNRNPA1 mRNA 3ʹUTR. Reporter assays, anti-miRNA and mutated miRNA-based assays, photoactivatable ribonucleoside-enhanced crosslinking and immunoprecipitation/reverse transcribed-quantitative polymerase chain reaction, and transient overexpression of miRNAs showed that miR-4745-5p and miR-6798-5p suppress hnRNP A1 protein levels via enhancement of binding to HNRNPA1 mRNA 3ʹUTR under serum/glucose-starved condition. miR-4745-5p and miR-6798-5p overexpression significantly decreased growth rates, which was rescued by co-transfection with anti-miRNA for miR-4745-5p and miR-6798-5p. Anti-miRNA transfection for miR-4745-5p and miR-6798-5p significantly increased growth rates under serum/glucose-starved conditions. Furthermore, hnRNP A1 overexpression recovered miR-4745-5p- and miR-6798-5p-induced growth suppression. These findings indicated that miR-4745-5p and miR-6798-5p are serum/glucose starvation-driven miRNAs for hnRNP A1 and validated the λN/boxB system as a simple and useful method for detecting mRNA 3ʹUTR-bound miRNA.